2014
DOI: 10.1016/j.gie.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic hemostasis is rarely used for hematochezia: a population-based study from the Clinical Outcomes Research Initiative National Endoscopic Database

Abstract: Background Data on use of endoscopic hemostasis performed during colonoscopy for hematochezia are primarily derived from expert opinion and case series from tertiary care settings. Objective To characterize patients with hematochezia who underwent in-patient colonoscopy and compare those who received endoscopic hemostasis with those who did not receive endoscopic hemostasis. Design Retrospective analysis Setting Clinical Outcomes Research Initiative (CORI) National Endoscopic Database 2002 – 2008 Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Other less common causes include colorectal polyps/neoplasms, Dieulafoy’s lesion, inflammatory bowel disease, and anorectal conditions including solitary rectal ulcer, radiation proctitis, and rectal varices. 56, 57 It is imperative to carefully inspect the colonic mucosa both on insertion and withdrawal since culprit lesions often bleed intermittently and may be missed when not actively bleeding. The endoscopist should intubate the terminal ileum to rule out proximal blood suggestive of a small bowel lesion.…”
Section: Colonoscopymentioning
confidence: 99%
“…Other less common causes include colorectal polyps/neoplasms, Dieulafoy’s lesion, inflammatory bowel disease, and anorectal conditions including solitary rectal ulcer, radiation proctitis, and rectal varices. 56, 57 It is imperative to carefully inspect the colonic mucosa both on insertion and withdrawal since culprit lesions often bleed intermittently and may be missed when not actively bleeding. The endoscopist should intubate the terminal ileum to rule out proximal blood suggestive of a small bowel lesion.…”
Section: Colonoscopymentioning
confidence: 99%
“…Colonic diverticular bleeding (CDB) is the most common cause of acute lower gastrointestinal bleeding (LGIB) 1,2 . LGIB can be serious and potentially lead to death 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with other studies, our data demonstrated that in most cases the etiology of LGIB is from benign pathologies such as diverticulosis, hemorrhoids and colonic ulcers. However, studies have demonstrated a 2-15% rate of finding colon neoplasm in patients presenting with lower GIB [ 15 , 16 ]. As a result, it is important to ensure appropriate outpatient evaluation to exclude malignant causes, particularly given the increased incidence of colon cancer in younger age groups, as younger age was shown to be predictive of discharge [ 17 ].…”
Section: Discussionmentioning
confidence: 99%